Diabetes Mellitus and Tuberculosis Treatment Outcomes in Pune, India. (4th March 2021) - Mave, Vidya; Gaikwad, Sanjay; Barthwal, Madhusudan; Chandanwale, Ajay; Lokhande, Rahul; Kadam, Dileep; Dharmshale, Sujata; Bharadwaj, Renu; Kagal, Anju; Pradhan, Neeta; Deshmukh, Sona; Atre, Sachin; et al.
Abstract: Background: Diabetes mellitus (DM) increases the risk of tuberculosis (TB) disease. Knowledge of the impact of DM on TB treatment outcomes is primarily based on retrospective studies. Methods: We conducted a prospective cohort study of new pulmonary TB patients with and without DM (TB-DM and TB only) in India. The association of DM with a composite unfavorable TB treatment outcome (failure, recurrence, mortality) over 18 months was determined, and the effect of DM on all-cause mortality and early mortality (death during TB treatment) was assessed. Results: Of 799 participants, 574 (72%) had TB only and 225 (28%) had TB-DM. The proportion of patients with DM who experienced the composite outcome was 20%, as compared with 21% for TB-only participants (adjusted hazard ratio [aHR], 1.13; 95% CI, 0.75–1.70). Mortality was higher in participants with DM (10% vs 7%), and early mortality was substantially higher among patients with DM (aHR, 4.36; 95% CI, 1.62–11.76). Conclusions: DM was associated with early mortality in this prospective cohort study, but overall unfavorable outcomes were similar to participants without DM. Interventions to reduce mortality during TB treatment among people with TB-DM are needed.